Electrocardiographic findings associated with early clinical deterioration in acute pulmonary embolism. (20th July 2022) - Weekes, Anthony J.; Raper, Jaron D.; Thomas, Alyssa M.; Lupez, Kathryn; Cox, Carly A.; Esener, Dasia; Boyd, Jeremy S.; Nomura, Jason T.; Davison, Jillian; Ockerse, Patrick M.; Leech, Stephen; Abrams, Eric; et al.
Abstract: Objectives: We sought to determine associations of early electrocardiogram (ECG) patterns with clinical deterioration (CD) within 5 days and with RV abnormality (abnlRV) by echocardiography in pulmonary embolism (PE). Methods: In this prospective, multicenter study of newly confirmed PE patients, early echocardiography and initial ECG were examined. Initial ECG patterns included lead‐specific ST‐segment elevation (STE) or depression (STD), T‐wave inversion (TWI), supraventricular tachycardia (SVT), sinus tachycardia, and right bundle branch block as complete (cRBBB) or incomplete (iRBBB). We defined CD as respiratory failure, hypotension, dysrhythmia, cardiac arrest, escalated PE intervention, or death within 5 days. We calculated odds ratios (ORs) for CD and abnlRV with univariate and full multivariate models in the presence of other variables. Results: Of 1676 patients, 1629 (97.2%) had both ECG and GDE; 415/1676 (24.7%) had CD, and 529/1629 (32.4%) had abnlRV. AbnlRV had an OR for CD of 4.25 (3.35, 5.38). By univariable analysis, the absence of abnormal ECG patterns had OR for CD and abnlRV of 0.34 (0.26, 0.44; p < 0.001) and 0.24 (0.18, 0.31; p < 0.001), respectively. By multivariable analyses, one ECG pattern had a significant OR for CD: SVT 2.87 (1.66, 5.00). Significant ORS for abnlRV were: TWI V2–4 4.0 (2.64, 6.12), iRBBB 2.63 (1.59, 4.38), STE aVR 2.42 (1.58, 3.74), S1‐Q3‐T3 2.42 (1.70, 3.47), and sinus tachycardia 1.68 (1.14, 2.49). Conclusions: SVT was an independent predictor of CD. TWI V2–4, iRBBB, STE aVR, sinus tachycardia, and S1‐Q3‐T3 were independent predictors of abnlRV. Finding one or more of these ECG patterns may increase considerations for performance of echocardiography to look for RV abnormalities and, if present, inform concerns for early clinical deterioration.